Garcilaso’s ‘Sedes ad cyprias’: a new source and a re-appraisal - Czepiel, M (Taylor & Francis, 2019)
Modern criticism has often neglected or been uncomplimentary about Garcilaso’s third Latin ode ‘Sedes ad cyprias’. This article presents a previously unidentified source for the poem, Erasmus’ translation of one of Lucian’s Dialogues of the Gods, and in the light of this offers a re-appraisal of Garcilaso’s poetic skill in the ode. Firstly, I discuss Garcilaso’s metrification and transformation of Erasmus’ prose translation. I go on to argue that his eclectic allusions to other Classical texts and the major changes he makes to the beginning and end of the source serve as part of a strategy of competitive imitation through which he tries to outdo the comic effect of Lucian’s dialogue.